2018
DOI: 10.1111/gove.12375
|View full text |Cite
|
Sign up to set email alerts
|

Representation beyond people: Lobbying access of umbrella associations to legislatures and the media

Abstract: Lobbying access to policy discussions determines how political interests are voiced and potentially exert influence. This article addresses whether access to the national legislature and the media favors umbrella organizations, which represent interests of their member groups. It theorizes that the role of umbrellas goes beyond signaling a large individual membership or constituency of people, but that umbrellas are distinct in transmitting interests from other organizations. This function is expected to be va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…First, compared to concentrated interests, representative diffuse organizations are as likely to be members of advisory councils, while solidarity groups have a lower likelihood of gaining access. These results are in line with previous research on interest group access which found that organized interests with informal constituencies of supporters enjoy less access compared to groups with formally affiliated members (Fraussen and Beyers 2015; Fraussen et al 2015; Junk 2019). Second, the extent to which organizations involve their constituencies has a positive effect on access.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First, compared to concentrated interests, representative diffuse organizations are as likely to be members of advisory councils, while solidarity groups have a lower likelihood of gaining access. These results are in line with previous research on interest group access which found that organized interests with informal constituencies of supporters enjoy less access compared to groups with formally affiliated members (Fraussen and Beyers 2015; Fraussen et al 2015; Junk 2019). Second, the extent to which organizations involve their constituencies has a positive effect on access.…”
Section: Discussionsupporting
confidence: 92%
“…Second, the extent to which organizations involve their constituencies has a positive effect on access. This corroborates recent research demonstrating that policy‐makers value organizations functioning as transmission belts between their constituencies and policy‐makers (Albareda and Braun 2019; Grömping and Halpin 2019; Junk 2019). Finally, politicization has a positive effect on the likelihood of gaining access for all group types, which confirms that access of organized interests to advisory councils is not predominantly depoliticized and technocratic in nature.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This body of literature provides several promising approaches to the study of transmission. These include, for example, studies that examine patterns in access to policy-making institutions (Colli, 2019;Junk, 2019) or scrutinize the type and framing of a message transmitted to other actors (De Bruycker, 2016;Voltolini & Eising, 2017). We add that especially the role of the media as a key actor in the transmission and (re)framing of a minipublic's recommendations deserves more attention (for a notable exception, see Parkinson, 2006).…”
Section: Trajectories For Future Researchmentioning
confidence: 99%
“…Yet, studies that focus on how specific organizational rules, structures, and mechanisms contribute to group preference formation are less common (for an exception, see Barakso & Schaffner, 2008). To be sure, an important strand of work on federated organizations (Minkoff et al, 2008; Skocpol et al, 2000) and, more recently, umbrella organizations (Berkhout et al, 2018; Fraussen & Beyers, 2016; Junk, 2019) has drawn scholarly attention to the role of organizational structure—although here the focus tends to be on other dependent variables (e.g., citizen participation, access to policy‐makers) 3 . This disparate body of research on interest group governance nonetheless aims to evaluate whether these groups are democratic.…”
Section: Interest‐aggregation and Agenda‐setting In Public Policy Res...mentioning
confidence: 99%